TOEFL PREPARATION IN EFL CLASS: STUDENTS’ PROBLEMS AND TEACHER’S STRATEGIES - Wahyuni, Nining; Alim, Condro Nur; Saefurohman, Saefurohman (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This research aimed to describe: students’ problems in TOEFL Preparation Class; strategies employed by the teacher to overcome the students’ problems; and how TOEFL Preparation Class should be organized to meet students’ need. Using a descriptive qualitative design, the study collected data through observation, questionnaires, interviews, and documentation. The findings revealed: (1) students faced two types of problems: specific difficulties in each section (limitations of memory, unfamiliar topics, difficulties to catch the speaker say, lack of grammar and vocabulary mastery and difficulty determining main ideas); general problems like less practice, fewer basic skill, lack of motivation, lack of concentration, and shortage preparation; (2) Strategies used by the teacher were: fun learning activities, providing access to TOEFL practice materials, drills and practice, tips and tricks, note-taking, reviewing tenses and grammar, skimming and scanning techniques, and structured assignments in LMS; (3) Developing the TOEFL Preparation Class to meet students’ needs involved: knowing students’ problems, analyzing student needs, selecting materials, determining teaching strategies, giving evaluation and feedback, providing resources and facilities, determining class schedule and duration, assessing results and effectiveness, and implementing continuous improvement.Keywords: TOEFL Preparation Class, Students’ Problems, Teacher’s Strategies